The study of relationship between social capital and self-rated health in Bandar Abbas, Iran - Hedayat Allah Nikkhah (Shahid Beheshti University of Medical Sciences, 2018)
Background: Health is a key component of an individual's welfare and the standard of living. Social capital has attained a considerable attention in science and policy making since researchers have suggested that it may have a positive impact on the well-being of individuals and the society. The aim of this study was to examine the relationship between social capital and self-rated health.   Methods: A cross-sectional study was conducted among individuals aged from 18 and older, who lived in Bandar Abbas city in 2017. The data used in this study obtained from a questionnaire with multi-stage random sample of respondents. The data were coded, computed, and analyzed by using SPSS software 16 (SPSS Inc., Chicago, IL, USA).   Results: A total of 255 respondents participated in the present study. Approximately 126 (49.4%) were male. The results obtained on age also report that the average age of respondents were equal to 30.08. Additionally, 126 (49.4%) of the respondents were married. The result of the correlation between self-rated health and socio-economic variables, such as income, education, and age confirmed that there was a statistically significant positive correlation between self-rated health and income (P<0.001) and age (P=0.043). The statistical analysis of t-test showed that the respondents who were married (P=0.01) and male (P=0.01) showed to be healthier compared to the single and female participants. The results also showed that social trust and social participation were positively associated with desirable self- rated health. Moreover, higher levels of trust and social participation were both associated consistently with high levels of self-rated health. Social trust was also associated positively with desirable self-rated health, after adjusting for the individuals' demographic factors and socioeconomic status (P=0.001).   Conclusion: Income and social trust have the most significant influence on self-rated health. Social trust as an indicator of social capital had a significant impact on the self-rated health of respondents. Social trust increases social health and reduces stress and anxiety in individuals.